The relationship between personality, theory of planned behaviour and physical activity in individuals with type II diabetes. Issue 13 (27th August 2008) - Davies, Cally A; Mummery, W Kerry; Steele, Rebekah M
Abstract : Objective: The purpose of the present study was to conduct a process analysis of the effects of personality on physical activity intention and behaviour using the theory of planned behaviour (TPB). Design: Prospective study design with data collected by means of two questionnaires. Methods: Data were obtained by means of two questionnaires, the initial questionnaire measured demographic characteristics, TPB constructs, physical activity intention and personality. The 2-week follow-up questionnaire assessed self-report physical activity behaviour. A series of regression analysis were undertaken to identify the relationship between the variables and to determine mediation effects of the TPB constructs. Patients: A random sample of individuals with type II diabetes was selected from the Diabetes Australia (Queensland) membership database. A total of 74 complete data sets were obtained. Results: Intention explained 28% of the variance in physical activity behaviour. Attitude, subjective norm and perceived behavioural control (PBC) explained 73% of variance in physical activity intention. Attitude and PBC mediated the relationship between conscientiousness and physical activity intention. Conclusions: These results provide preliminary evidence that targeting constructs proximal to the behaviour (attitudes and PBC) may be effective in overcoming inherent qualities such as personality in order to produce physical activity behaviour change within this sample population.